Periodic array of regular Ag nanoparticle trimers: a reliable polarization-independent surface-enhanced Raman spectroscopy substrate. Issue 86 (2nd September 2016) - Feng, Chao; Zhao, Yan; Jiang, Yijian
Abstract : A large-area periodic array of regular Ag nanoparticle trimers was fabricated, it possesses polarization-independent SERS performance. Abstract : A large-area periodic array of regular Ag nanoparticle trimers was fabricated. This array offered reliable polarization-independent surface-enhanced Raman spectroscopy (SERS) performance for practical macroscopic detection. In polarized SERS experiments for macroscopic detection, it was found that, for any random incident polarization within the full 360° range, the periodic array of regular Ag nanoparticle trimers always outputted an undifferentiated SERS signal with a stable intensity. Finite-difference time-domain simulations showed that the reliable polarization-independent performance of the periodic Ag nanoparticle array arises from the unique structure of the regular nanotrimers. It was found that the polarized SERS characteristic of any single probe-adsorption position is polarization-dependent, but the structure of the regular Ag nanoparticle trimers could hybridize the totally polarization-dependent SERS signals from every single probe-adsorption position to form a polarization-independent SERS signal. This periodic array of regular Ag nanoparticle trimers was thus shown to be a reliable and reproducible SERS substrate with the potential to allow convenient and flexible macroscopic SERS detection outside of the laboratory setting without requiring an optimal incident polarization.